CO-HOUSING: A SOLUTION TOWARD SUSTAINABLE SETTLEMENT IN BATAM CITY - Elva Christina; Gladies Imanda Utami Rangkuty (Journal of Architectural Research and Education, 2022)
The increasing population urges the need for space as a place to live in urban areas with limited land. In addition, the population of Batam City are dominated by millennials with low financial ability but high social capital. That can trigger the construction of illegal houses, which sometimes do not meet the criteria for settlements that are slums, reaching fifteen hectares in the Belian Village of Batam City Sub-District. It is necessary to adapt collaborative housing (co-housing) with minimal land use. However, it can provide space as a place to live and socialize as much as possible, including residents in building management. The methodology of this research is a qualitative method with a descriptive approach to the condition of the city of Batam, which is observed directly by paying attention to the strengths, weaknesses, opportunities, and threats, as well as co-housing design considerations. Thus, this study resulted in recommendations for the design of co-housing buildings with facilities and features close to the site, spatial layout and planning that are to the needs of the target user, a property model that is by the user's abilities, and screening and curation process that the user can accept. The sustainability of settlements can also be the result of adapting the co-housing concept in Batam.